KETERKAITAN KETERSEDIAAN ANUGERAH LOKAL DENGAN KETIMPANGAN ANTAR WILAYAH PADA SEKTOR PERTANIAN DI KABUPATEN SEMARANG - Lyra Bumantara Syarif (MediaTrend, 2018)
Agriculture as the oldest economic sector in the world is a potential catalyst to reduce disparities between regions, especially in developing countries which are the livelihoods of the citizens are mostly very much dependent in agricultural sector. Nevertheless the efforts to make the agricultural sector as a catalyst for reducing the disparities between regions in developing countries until now is constrained with the productivity level of agricultural sector that is still low due to the high dependency on the availability of local endowments. As for with low productivity level of the agricultural sector surely will be impacted on the extent of the disparities between regions. Hence, this research trying to analyze how big the influence of local endowments (which is represented with the size of farmland and the amount of agricultural labour), are affecting the disparity of agricultural sector between regions in Semarang Regency that will be focused on years 2008-2011.